2006
DOI: 10.1373/clinchem.2005.063545
|View full text |Cite
|
Sign up to set email alerts
|

Breath Analysis: Potential for Clinical Diagnosis and Exposure Assessment

Abstract: Breath tests are among the least invasive methods available for clinical diagnosis, disease state monitoring, and environmental exposure assessment. In recent years, interest in breath analysis for clinical purposes has increased. This review is intended to describe the potential applications of breath tests, including clinical diagnosis of diseases and monitoring of environmental pollutant exposure, with emphasis on oxidative stress, lung diseases, metabolic disorder, gastroenteric diseases, and some other ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
243
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(251 citation statements)
references
References 115 publications
(113 reference statements)
0
243
0
8
Order By: Relevance
“…This is one reason to test the reactive paper spray method of analysing aldehydes with both benchtop and portable mass spectrometers. Breath analysis by mass spectrometry is an area of increasing interest due to its capability for making non-invasive measurements [35][36][37] which can be used to monitor metabolic state and potentially detecting disease biomarkers [38][39][40]. It is in this context that we describe a fast, direct and reactive paper spray approach to determine aldehydes using in-situ derivatization with 4-aminophenol to produce iminium ions.…”
Section: Introductionmentioning
confidence: 99%
“…This is one reason to test the reactive paper spray method of analysing aldehydes with both benchtop and portable mass spectrometers. Breath analysis by mass spectrometry is an area of increasing interest due to its capability for making non-invasive measurements [35][36][37] which can be used to monitor metabolic state and potentially detecting disease biomarkers [38][39][40]. It is in this context that we describe a fast, direct and reactive paper spray approach to determine aldehydes using in-situ derivatization with 4-aminophenol to produce iminium ions.…”
Section: Introductionmentioning
confidence: 99%
“…The band at 942 cm -1 can be assigned to the stretching mode of W=O terminal bonds indicating surface tungsten hydrates [10,11]. Peaks at 203, 272, 303, 370, 425, 642, 688 and 805 cm -1 belong to the Δ phase of WO 3 .…”
Section: As-sprayed Powdersmentioning
confidence: 99%
“…Nitric oxide belongs to the class of inorganic gaseous chemicals found in exhaled breath and is characterized as a signaling biomarker for disease [1][2][3]. The diagnostic value of exhaled NO measurements to differentiate between healthy persons with or without respiratory symptoms and patients with confirmed asthma has been established by Dupont who showed that >16 ppb of NO in lower respiratory tract could be treated as a cutoff for asthma with a 90% specificity and 90% positive predictive value [4].…”
Section: Introductionmentioning
confidence: 99%
“…For the sensor systems in this work, the Stern-Volmer [eqn (1)] and the two-site Demas model [eqn (2)] were employed to analyse the O 2 data.…”
Section: Sensor Response Behavior For O 2 Detectionmentioning
confidence: 99%